Adsorption of Pb(II) Using Magnetic Titanate Nanotubes Prepared via Two‐Step Hydrothermal Method. Issue 7 (18th November 2013) - Zhang, Lei; Wang, Xin; Chen, Huan; Jiang, Fang
<x xml:space="preserve">Abstract</x> Magnetic titanate nanotubes (MTNTs) have been prepared by a two‐step hydrothermal method and used as adsorbents for the removal of Pb(II) from aqueous solution. The MTNTs are characterized by N2 adsorption–desorption analysis, transmission electron microscopy, powder X‐ray diffraction, vibrating sample magnetometer, zeta potentials analysis, X‐ray photoelectron spectra (XPS), and Fourier transform infrared (FT‐IR) spectroscopy. The results indicate that CoFe2O4 is formed in the hydrothermal process and implanted into the entangled network of nanotubes. The saturation magnetization of MTNTs is 9.20 emu g−1, which makes MTNTs can be readily recovered in an external magnetic field. The adsorption of Pb(II) over MTNTs is very fast and follows the pseudo‐second‐order kinetic model. Additionally, Pb(II) adsorption is strongly pH dependent and the maximum adsorption capacity of MTNTs for Pb(II) reaches 442.5 mg g−1 at pH 5.0. FT‐IR and XPS analysis suggest that the adsorption mechanism of MTNTs is ionic exchange between Pb(II) and Na+/H+ in the interlayer of nanotubes. Furthermore, Pb(II)‐loaded MTNTs can be regenerated by saturated EDTA‐2Na solution at pH 2.5 and the adsorbents can be used repeatedly.